1984
DOI: 10.1083/jcb.99.2.723
|View full text |Cite
|
Sign up to set email alerts
|

An enzyme that removes clathrin coats: purification of an uncoating ATPase.

Abstract: Uncoating ATPase, an abundant 70,000-mol-wt polypeptide mediating the ATPdependent dissociation of clathrin from coated vesicles and empty clathrin cages, has been purified to virtual homogeneity from calf brain cytosol . Uncoating protein is present in cells in amounts roughly stoichiometric with clathrin . This enzyme is isolated as a mixture of monomers and dimers, both forms being active . ATP can support protein-facilitated dissociation of clathrin at micromolar levels; all other ribotriphosphates as well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
228
0
2

Year Published

1991
1991
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 421 publications
(242 citation statements)
references
References 47 publications
12
228
0
2
Order By: Relevance
“…S1). This agrees well with previous studies that have shown Hsc70 bound to the free triskelia (14,15,22) and supports the idea previously proposed that Hsc70 acts to chaperone the released clathrin triskelia back to the plasma membrane (25), preventing formation of empty cages within the cell. It should be noted that, in a similar previous study, Schuermann et al (22) also observed a second, slower linear phase of disassembly following the initial fast exponential phase.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…S1). This agrees well with previous studies that have shown Hsc70 bound to the free triskelia (14,15,22) and supports the idea previously proposed that Hsc70 acts to chaperone the released clathrin triskelia back to the plasma membrane (25), preventing formation of empty cages within the cell. It should be noted that, in a similar previous study, Schuermann et al (22) also observed a second, slower linear phase of disassembly following the initial fast exponential phase.…”
Section: Discussionsupporting
confidence: 82%
“…It has been proposed that three molecules of Hsc70 are involved in removing one triskelion from a coated vesicle (13). This is supported by electron microscopy and gel filtration data that showed three Hsc70 molecules bound to the released triskelia (14,15) and by demonstration of maximal binding to cages of three Hsc70s per triskelion (16). However, interestingly, Xing et al (17) report a stoichiometry of about one Hsc70 molecule per threefold clathrin vertex in their recent cryoelectron microscopy study of Hsc70 bound to clathrin cages.…”
mentioning
confidence: 62%
“…Proteins of the HSP70 family, including Hsc70, have been shown to function as intracellular chaperones with essential roles in protein synthesis, folding and assembly, trafficking, and degradation (Daugaard et al 2007). Hsc70 has also been implicated in various stages of clatherin-mediated endocytosis (Schlossman et al 1984;Newmyer et al 2003;Eisenberg and Greene 2007), antigen presentation (Zhou et al 2005;Kamiguchi et al 2008), and protection from apoptosis (de la Rosa et al 1998;Dastoor and Dreyer 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Effects of depletion of ATP on vesicle binding and NE assembly. Sperm were incubated in S20o (,4 and B) or S20o plus sucrosepurified NEP-A (C and D) for 60 min at 18°C in the presence of an ATP-depleting system (Schlossman et al, 1984) (A and C) or an ATP-regenerating system (B and D). Vesicles attach to the chromatin surface in an ATP-independent manner (A-C) whether NEP-A is present or not (A and C).…”
Section: Discussionmentioning
confidence: 99%